Current barriers to initiating insulin therapy in individuals with type 2 diabetes - Galdón Sanz-Pastor, Alba; Justel Enríquez, Alicia; Sánchez Bao, Ana; Ampudia-Blasco, Francisco Javier (Frontiers in Endocrinology, 2024)
Insulin is an essential drug in the treatment of diabetes, often necessary for managing hyperglycemia in type 2 diabetes mellitus (T2DM). It should be considered in cases of severe hyperglycemia requiring hospitalization, after the failure of other treatments, in advanced chronic kidney disease, liver cirrhosis, post-transplant diabetes, or during pregnancy. Moreover, in specific patient subgroups, early initiation of insulin is crucial for hyperglycemia control and prevention of chronic complications. Clinical guidelines recommend initiating insulin when other treatments fail, although there are barriers that may delay its initiation. The timing of initiation depends on individual patient characteristics. Typically, insulinization starts by adding basal insulin to the patient’s existing treatment and, if necessary, progresses by gradually introducing prandial insulin. Several barriers have been identified that hinder the initiation of insulin, including fear of hypoglycemia, lack of adherence, the need for glucose monitoring, the injection method of insulin administration, social rejection associated with the stigma of injections, weight gain, a sense of therapeutic failure at initiation, lack of experience among some healthcare professionals, and the delayed and reactive positioning of insulin in recent clinical guidelines. These barriers contribute, among other factors, to therapeutic inertia in initiating and intensifying insulin treatment and to patients’ non-adherence. In this context, the development of once-weekly insulin formulations could improve initial acceptance, adherence, treatment satisfaction, and consequently, the quality of life for patients. Currently, two once-weekly basal insulins, insulin icodec and basal insulin BIF, which are in different stages of clinical development, may help. Their longer half-life translates to lower variability and reduced risk of hypoglycemia. This review addresses the need for insulin in T2DM, its positioning in clinical guidelines under specific circumstances, the current barriers to initiating and intensifying insulin treatment, and the potential role of once-weekly insulin formulations as a potential solution to facilitate timely initiation of insulinization, which would reduce therapeutic inertia and achieve better early control in people with T2DM.